ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN SERTA PENGARUHNYA TERHADAP KEWAJARAN PENYAJIAN LAPORAN KEUANGAN PADA PT MITRA ANDALAN SATKOMINDO - Zulkarnain Moeshak Zen; Widodo Widodo; Rini Meilinda (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This thesis aims to determine the application of the recognition of revenues and expenses on the fairness of financial statements and whether the methods used are in accordance with the Financial Accounting Standards. Jakarta The method used is a qualitative research method. The data used in this research is secondary data (financial statement of PT Mitra Andalan Satkomindo Years 2013-2014). The results obtained by treatment of the recognition of revenues and expenses of PT Mitra Andalan Satkomindo said is not in accordance with Financial Accounting Standards because it still uses the cash basis method, whereby revenue is recognized when cash is received and expenses are recognized when cash is excluded. The conclusion of this research is PT Mitra Andalan Satkomindo has been applying cash basis method in the recognition of revenue and expenses not in accordance with Financial Accounting Standards. There are discrepancies in the presentation of financial statements because the company only presents the income statement only. Then there are also discrepancies in the treatment of the recognition of income and expenses Financial Accounting Standards with PT Mitra Andalan Satkomindo which resulted in 2013 PT Mitra Andalan Satkomindo experienced overstated Rp. 28.52 million and in 2014 also had overstated Rp. 40.35 million. Advice can be given by the author is better in terms of the recognition of revenues and expenses of PT Mitra Andalan Satkomindo using the accrual basis. Recording the recognition of revenues and expenses based on the cash basis is not appropriate with the Financial Accounting Standards for revenue and expenses are not recognized in a period should be. So as long as PT Mitra Andalan Satkomindo based on primary data obtained by the authors do not describe the accuracy of the financial information. With accrual transactions are recorded and reported on the events and not when cash is paid (received). In presenting the financial statements of PT Mitra Andalan Satkomindo should also make the Balance Sheet, Income Statement, Statement of Changes in Equity, Cash Flow Statement, and Notes to Financial Statements. Thus financial reports can provide accurate financial information about the financial position. Then the company must implement accrual basis at each recording transactions in order not to cause a disparate impact on the treatment of income and expenses that their income and expenses reported in the condition (overstated) than necessary.